Pemantauan Kondisi Polusi Udara Secara Real Time Di Kawasan Universitas Riau Dengan Menggunakan Wireless Sensor Network Waspmote Dan Zigbee - Feri Saputra; Yusnita Rahayu; Ery Safrianti (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
Air quality monitoring is very necessary to anticipate the dangerous air pollution such as forest fires pollution like PM10. Excellent air monitoring done in real time, so that the monitoring data obtained directly. In the research make aplication air monitoring real time using Microsoft Visual Basic 2010, air monitoring device with using wireless sensor network waspmote plug and sense for monitoring of PM10 and waspmote OEM for monitoring CO and O3, data communication using Zigbee. Application will process wireless sensor network waspmote data to ISPU data for reference condition the air content PM10, CO dan O3, and application will display in ISPU graphical. Design database in Microsoft Access to connect monitoring aplication so monitoring data can be stored. Air monitoring conducted in Riau University.Keywords : Wireles Sensor Network Waspmote, Zigbee, Database, Real time, Air polution